The Role of the Social Worker in Educating Patients about Their Rights - Hassan Ali Mansi Al-Ghamdi; Saad Mohammed Dhef Allah Al-Ghamdi; Ali Mohammed Ameesh Al-Ghamd (International Journal of Medical Toxicology and Legal Medicine, 2024)
Social work is considered a specialized professional field that emerged from human concerns across the world. However, it is a human endeavor that has existed since the emergence of human society in the form of empathy, solidarity, and cooperation among individuals within the community. Social work has undergone various developments over time, evolving into a profession based on scientific principles and methodologies that aim at improving human dignity and welfare. (Abid, 2010, 13). Medical social work is one of the important areas of social work practiced in medical institutions, where the social worker helps the patient benefit from the resources and services of the institution. This enhances the social performance of the patient and highlights the significance of the collaboration between the medical institution and social services to provide optimal medical care for the patient, thus facilitating recovery and improving their social functioning, which ultimately helps both the individual and the community.